Association between phase angle and the nutritional status in pediatric populations: a systematic review - Franco-Oliva, Andrea; Ávila-Nava, Azalia; Rodríguez-Aguilar, Estíbaliz Amairani; Trujillo-Mercado, Ander; García-Guzmán, Alda Daniela; Pinzón-Navarro, Beatriz Adriana; Fuentes-Servín, Jimena; Guevara-Cruz, Martha; Medina-Vera, Isabel (Frontiers in Nutrition, 2023)
Background and Aims: Malnutrition is prevalent in pediatric population with any disease, and is related to changes in body composition, in addition, recent studies have documented relationship between these changes and the phase angle (PhA), that is an important parameter of functional nutritional assessment. PhA could be a new marker of nutritional status. In fact, many studies have generated information about the association between PhA and malnutrition in various pathologies, most of the information being in the adult population. Our objective was to summarize the evidence on the association of PhA with nutritional status in pediatric populations. Methods: A systematic search in the Medline/PubMed, and LILACS databases for studies published up to October 2022. Studies were included with the following criteria: performed on pediatric subjects, reporting relation of PhA with nutritional status with any objective nutritional indicator, and PhA measured by electric impedance and reported at 50 kHz. Data were synthesized from the studies that reported cut-off analysis of PhA with ROC curve, comparison of PhA means compared by nutritional status strata and studies that reported correlation values between PhA values and nutritional status indicators. Risk of bias was assessed using the Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies and Quality Assessment of Diagnostic Accuracy Studies. Results: Of the 126 studies identified in the search, 15 met the inclusion criteria and were included in this review. The included studies report the association between PhA values and objective indicators of nutritional status. The indicators nutritional status used were: WAZ for malnutrition, HAZ for malnutrition-stunting, BMI for starvation state, BMIz and BMI for malnutrition, MUAC for SAM, FFMIz for moderate malnutrition, among other. Conclusions: The early identification of malnutrition is relevant to establish nutritional treatment correctly; PhA appears to be a sensitive indicator of nutritional status and is easy to obtain it. Although the results of this review are inadequate yet to establish a cut-off point for PhA associated with malnutrition in pediatric populations, however in most of the studies an association was observed between the PhA values and the objective indicators of nutritional status. Systematic Review Registration: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022362413